(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
First results and basic geological information of the Seceda Coring Project are reported. The Seceda project started with drilling of a well for scientific purposes. The core material is currently studied by an international group of geoscientists from different universities. Fundamental topics of the project are a thorough sedimentological and cyclostratigraphic analysis of the complete succession of Middle Triassic pelagic Buchenstein Beds in the northwestern Dolomites (Southern Alps, Italy) as well as their temporal relationship with coeval carbonate platforms. Complementary studies focus on stratigraphic correlation tools including bio-, litho- and magnetostratigraphy.